Clustering of Food Security Levels in North Aceh Using K-Medoids - Tarisha Zhafira; Bustami Bustami; Nunsina Nunsina (Journal of Applied Informatics and Computing, 2026)
Food security is essential for ensuring food availability, accessibility, and utilization. This study applies a multidimensional indicator framework covering social, economic, and infrastructure aspects to cluster regions in North Aceh Regency, addressing limitations of previous studies that primarily focus on agricultural production indicators and lack policy-oriented analysis. The analysis uses 2023 data from 27 sub-districts at the village level, comprising 852 villages. The indicators include: (1) the ratio of agricultural land area to total population, (2) the ratio of food supply facilities and infrastructure to households, (3) the ratio of population with the lowest welfare status to total population, (4) the proportion of villages without adequate transportation access via land, water, or air, (5) the ratio of households without access to clean water, and (6) the ratio of population per health worker relative to population density. Data processing involves preprocessing, normalization, and K-Medoids clustering, evaluated using the Davies–Bouldin Index (DBI) and Silhouette Coefficient (SC). The results identify six clusters: highly food insecure (C1) with 63 villages, food insecure (C2) with 92 villages, moderately food insecure (C3) with 179 villages, moderately food secure (C4) with 42 villages, food secure (C5) with 49 villages, and highly food secure (C6) with 427 villages. Most villages fall within moderately food insecure to highly food secure categories, indicating disparities in food security distribution. The DBI value of 3.085 indicates moderate cluster compactness, while the SC value of 17.75% suggests weak separation between clusters. These findings provide policy recommendations for targeted and equitable food security interventions.